2018
DOI: 10.1016/j.jtumed.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Self-care model application to improve self-care agency, self-care activities, and quality of life in patients with systemic lupus erythematosus

Abstract: Objectives This study aimed to examine the effect of the application of a self-care model to improve self-care agency (SCA), self-care operation, and quality of life (QoL) in patients with systemic lupus erythematosus (SLE). Methods This study employed a pre-experimental design with one pretest-posttest group. Thirty-six respondents were selected through total sampling. The experimental group was provided self-care management training, followed by four weekly home visit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 22 publications
(32 reference statements)
2
9
0
8
Order By: Relevance
“…The low level of education can prevent a person from digesting information related to knowledge. The level of education greatly influences the respondent's knowledge regarding diabetes mellitus disease, both the complications that occur in hypoglycemia and their discussion [34][35][36]. Based on the above results for health education regarding diabetes mellitus, most respondents have never received health education because there are rarely meetings in that area, so that health education is rarely given to families.…”
Section: Characteristics Of Diabetes Mellitus Familymentioning
confidence: 99%
“…The low level of education can prevent a person from digesting information related to knowledge. The level of education greatly influences the respondent's knowledge regarding diabetes mellitus disease, both the complications that occur in hypoglycemia and their discussion [34][35][36]. Based on the above results for health education regarding diabetes mellitus, most respondents have never received health education because there are rarely meetings in that area, so that health education is rarely given to families.…”
Section: Characteristics Of Diabetes Mellitus Familymentioning
confidence: 99%
“…A large number of health programs have been developed to improve patients’ self-care ability. These are mostly disease-specific and often based on Orem’s nursing theory of self-care [45, 4751]. This theory is based on the assumption that people have a natural ability for self-care, and nursing should focus on improving self-care behavior.…”
Section: Introductionmentioning
confidence: 99%
“…As the self-care power increased in the previous studies, it was found that the quality of life increased statistically highly signifi cantly [12][13][14]. Therefore, it is recommended that EBT should be included during regular screening surveillance to avoid any delay in diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%